Improving variant interpretation and diagnosis in Koolen-de Vries syndrome through a curated genotype–phenotype repository - Hailin Huang; Jia Geng; Yang Long; Wenyu Xiong; Xiaolu Wang; Chao Wang; Qian Zhang; Ting Tang; Yuxin Chen; Yu Zhao; Jing Cheng; Yu Lu; et al. (Molecular Genetics and Genomics, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

An entomopathogen-based small-RNA delivery system promotes the biocontrol efficacy against termites - Chen-Chen Zhao; Hang Lu; Xiao-Long Mao; Long-Long Sun; Fang-Chan He; Zheng-Xun Lv; Qing-Bo Tang; Cheng-Wei Li; Long Liu (Pesticide Biochemistry and Physiology, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Electron injection-induced MoS2 phase transition from 2H to 1T via alkylamine intercalation for enhanced sodium-ion storage - Xinglong Gao; Chong Hu; Long Zhang; Wenxin Tang; Mingzhi Wei; Lingli Cheng; Zhen Li (Chemical Engineering Journal, 2026)

Failure behavior of composite curved sandwich structures with 3D-printed reinforced-truss pyramidal lattice core - Jian Tang; Zhihao Xie; Long Zhang; Yiru Ren; Fei Cheng; Hongyong Jiang (Ocean Engineering, 2026)

SETD2 governs the regenerative threshold in the liver by gating STAT5-dependent Cox2 signaling - Liping Luo; Ting Chen; Yanzhu Long; Cheng Wang; Peipei Li; Xiaoqi Zhou; Zhengming Du; Tonglang Tang; Jinxuan Wang; Qingliang Zou; Limao Xu; Bo Liu; et al. (Science China Life Sciences, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Blackwellomyces napialus (Cordycipitaceae, Hypocreales), a Novel Species Parasitic on Napialus hunanensis from China - Jin-Long Jia; Cui-Yuan Wei; Mei Tang; Zhu-Yu Cheng; Ya-Nan Wang; Zhu-Liang Yang; Gang Deng; Yuan-Bing Wang (Current Microbiology, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Slope and grain size control on channel-levee development in mixed turbidite-contourite systems - Long He; Tao Jiang; Man Tang; Dongmei Tian; Licheng Cao; Cong Cheng (Marine Geology, 2026)

Association of plasma metals with total burden of cerebral small vessel disease: Evidence from China - Lei Zheng; Hao-Long Zeng; Ying Hui; Feipeng Cui; Yudiyang Ma; Jianing Wang; Linxi Tang; Meiqi Xing; Shuohua Chen; Liming Cheng; Shouling Wu; Zhenchang Wang; et al. (Journal of Hazardous Materials, 2026)

Function and mechanisms of polyethylene glycol-modified sodium acrylate-acrylamide hydrogel for microalgal biomass enrichment and purification - Cong-Cong Tang; Qiao Zhong; Yi Liu; Yong-Qi Cheng; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2026)

miR-19b-3p regulates autophagy of BMSCs in hypoxia through PTEN/Akt/mTOR pathway to promote fracture healing - Shouyu Xiang; Wei Liu; Cheng Tang; Chuhai Xie; Hailan Hu; Jianhui Zhou; Yanming Cao; Long Ling (Journal of Molecular Histology, 2026)

Genetic and transcriptomic identification of WPG1 controlling nitrogen allocation-related leaf chlorisis and premature senescence in wheat - Haili Zhang; Li’ao Zhang; Qiang Li; Ling Yi; Juanyu Zhang; Yanyan Tang; Jinhui Wang; Junjun Liang; Tao Li; Fangyan Zhang; Yiran Cheng; Yi Wang; et al. (Theoretical and Applied Genetics, 2026)

Real-time Monitoring Unveils Three Distinct Neuronal Response Patterns to SAW Ultrasound via L-type Calcium Channels - Yiming Chen; Wenxu Tang; Yifan Wang; Ya Gao; Jiaqi Hu; Yixuan Lu; Long Meng; Hairong Zheng; Yi Feng; Liming Cheng; Wenyong Fan; Qian Cheng; et al. (Neuroscience Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Resilience of human mobility in response to unexpected events - Junqing Tang; Jixiang Liu; Jiangping Zhou; Long Cheng; Wenjia Zhang; Mengqi An (Journal of Transport Geography, 2025)

Electronic structure engineering of Fe/Co dual-atom catalysts enhances ultrafast Fenton-like reactions mediated by high-valent iron-oxygen-cobalt bridged complexes for safe pollutant removal - Huan Cheng; Peng Wei; Mingjia Liu; Yunhui Yang; Long Huang; Jian Tang; Rong Hu (Journal of Hazardous Materials, 2025)

Negative-pressure induced controllable foaming reaction for ultralight and flame-retardant phenyl-containing silicone rubber foam nanocomposites modified with low content of graphene oxide - Shuai-Chi Liu; Yun-Hao Qu; Dun-Peng Bao; De-Mei Kong; Zhi-Hao Xu; Zuan-Yu Chen; Yang Li; Jie-Feng Gao; Yong-Qian Shi; Pingan Song; Guo-Dong Zhang; Long-Cheng Tang (Chemical Engineering Journal, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

The effects of pond purification system on intestinal function of channel catfish (Ictalurus punctatus): a focus on intestinal development, digestion and absorption, and junction integrity - Zhong-Bing Zheng; Yu Yang; Jun Liu; Ming-Cheng Zhou; Ju-Hua Li; Long-Jiang Tang; Hai-Long Nie; Kang-Sheng Chen; Feng Liu; Xiang-Ning He; Zhi-Yuan Lu (Frontiers in Marine Science, 2025)
Pond purification system (PPS) is an outdoor aquaculture system designed based on recirculating aquaculture system (RAS) principles, utilizing recirculating water technology, which can achieve large-scale fish farming in the recirculating water system. The purpose of this experiment is to investigate the alterations in growth performance, intestinal histology, digestion-absorption function, and structural integrity of channel catfish raised in PPS. The findings indicated a significant optimization in water quality indicators pertinent to aquaculture, including total nitrogen, total phosphorus, chemical oxygen demand (COD), ammonia nitrogen, nitrite, and dissolved oxygen. Additionally, the growth performance of channel catfish reared in the PPS group was markedly improved. The intestinal morphology of these channel catfish exhibited increased villus height and a reduced number of mucus cells. Furthermore, serum levels of diamine oxidase and D-lactic acid were significantly decreased in channel catfish raised in the PPS group, while the expression of genes related to the apical junction complex was significantly upregulated, suggesting improved intestinal structural integrity. Moreover, the activities of digestive and absorptive enzymes, such as trypsin, amylase, lipase, and Na + -K + -ATPase, were elevated, indicating enhanced digestive and absorptive functions. In conclusion, based on the conditions of this experiment, the pond purification system module used in this study can effectively improve the quality of the aquaculture water, enhance fish growth performance and improve their intestinal health.

Integrating morphology, ecology, and genomics: Unraveling the population genetic and evolution within the Rosa graciliflora complex - Jia Miao; Liang-Ying Li; Zhen-Long Liang; Yu Feng; Cheng Zhang; Shi-Qi Li; Heng-Ning Deng; Jian Ru; Zhong-Yu Tang; Xin-Fen Gao (Molecular Phylogenetics and Evolution, 2025)

Calycosin alleviates ovariectomy-induced osteoporosis by promoting BMSCs autophagy via the PI3K/Akt/mTOR pathway - Shouyu Xiang; Yinji Luo; Wei Liu; Cheng Tang; Tianyu Zhu; Lai Tian; Tiansheng Zheng; Long Ling; Mingyang Jia; Xing Li; Yanming Cao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Cleaner purification of contaminants on cotton substrate interfaced with supercritical carbon capsules for sustainable development in cleaning industries - Meng-Yue Li; Fan Wang; An-Tong Liu; Qing-Cheng Tang; Xue Dong; Jia-Jie Long (Process Safety and Environmental Protection, 2025)

A spatiotemporal mixed-enhanced generative adversarial network for radar-based precipitation nowcasting - Long He; Kun Zheng; Huihua Ruan; Shuo Yang; Jinbiao Zhang; Cong Luo; Siyu Tang; Yunlei Yi; Yugang Tian; Jianmei Cheng (Computers & Geosciences, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Application of 3-D inversion of AMT data in exploration of concealed nonmetallic deposits: A Case Study on the Huashitou Mountain fluorite deposit in Beishan metallogenic belt, China - Jianhui Hu; Liuyang Xu; Yaotian Yin; Xu Jia; Ping Qi; Zhan Liang; Peng Su; Cheng Liu; Weidong Tang; Long Chen; Yanzhou Wang; Lin Liu (Journal of Applied Geophysics, 2025)

Rapid gelation of mechanical robust, conductive, and self-healing lignocellulosic nanofibrils hydrogel toward flexible sensor over a broad temperature spectrum - Zhi-Chao Xu; Yu-Qin Yang; Xiao-Wen Pang; Baiyu Jiang; Peng-Fei Mao; Li-Xiu Gong; Binghao Wang; Li Peng; Long-Cheng Tang; Shi-Neng Li (Chemical Engineering Journal, 2025)

Relationship between Th17 cell proportion and IL-17/-18 levels and disease progression in patients with multiple myeloma - Wen Liu; Jing Zhu; JiBing Cheng; Qian Tang; SiQi Long (Molecular & Cellular Toxicology, 2025)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Threshold effects of vegetation cover on production-living-ecological functions coordination in Xiangyang City, China - Chao Liu; Meijing Hao; Niwen Tang; Xun Liang; Long Cheng (Environmental Monitoring and Assessment, 2024)

Seawater corrosive engineering assisted in-situ room temperature synthesis of Ni/Co/Fe trimetallic composition to achieve polyester plastics upgrading and green hydrogen production - Zhao-Hui Zhang; Zhi-Ran Yu; Yi Zhang; Alexandre Barras; Ahmed Addad; Pascal Roussel; Long-Cheng Tang; Sabine Szunerits; Rabah Boukherroub (Chemical Engineering Journal, 2024)

Se-vacancy porous ultrathin ZnSe nanosheet/carbon composite for sodium storage via electron beam irradiation strategy - Chaoyan Jiang; Long Zhang; Xinglong Gao; Wenze Yu; Chong Hu; Wenxin Tang; Zhen Li; Lingli Cheng; Minghong Wu (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Photothermal flows activated CsPbBr3 ⊆ Pb-TCPP S-scheme heterojunction: In-situ converted interface for robust CO2 reduction coupling with benzylamine oxidation - You-Guo Luo; Cheng-Long Peng; Luo-Bing Tang; Jian-Yong Zhang; Hao-Zhi Wang; Yu-Feng Liu; Qin-Fei Ke; Yong-Zheng Fang; Na Zhang (Chemical Engineering Journal, 2024)

Assessing the causal relationship between immune cells and prostatitis: evidence from bidirectional mendelian randomization analysis - Genyi Qu; Weimin Jiang; Zhaohui Long; Xing Zhou; Yijie Wang; Guang Yang; Cheng Tang; Yong Xu (Mammalian Genome, 2024)

Establishment and characterization of the PDAC-X3 cell line: a novel Chinese-origin pancreatic ductal adenocarcinoma cell line - Changpeng Chai; Huan Tang; Xin Miao; Yuanhui Su; Lu Li; Cheng Yu; Jianfeng Yi; Zhenzhen Ye; Long Miao; Bo Zhang; Zhengfeng Wang; Wei Luo; et al. (Human Cell, 2024)

Large-scale and facile fabrication of phenyl-containing silicone foam materials with lightweight, wide-temperature flexibility and tunable pore structure for exceptional thermal insulation - Yu-Yue Wu; Zhi-Hao Wu; Zuan-Yu Chen; Li-Dong Peng; Zi-Qi Guan; Yang Li; Cheng-Fei Cao; Guo-Dong Zhang; Jie-Feng Gao; Pingan Song; Yong-Qian Shi; Long-Cheng Tang (Chemical Engineering Journal, 2024)

Early warning for thermal runaway in lithium-ion batteries during various charging rates: Insights from expansion force analysis - Kuijie Li; Long Chen; Xuebing Han; Xinlei Gao; Yao Lu; Depeng Wang; Shun Tang; Weixin Zhang; Weixiong Wu; Yuan-cheng Cao; Languang Lu; Jinyu Wen; et al. (Journal of Cleaner Production, 2024)

Geometric and electronic engineering of cobalt, manganese oxide sites in porous nitrogen-doped carbon for boosted oxygen reduction activity in microbial fuel cell - Wenyi Wang; Long Tang; Cheng Chen; Wencong Sun; Yuanyuan Wang; Xueqin Wang (Journal of Environmental Chemical Engineering, 2024)

Metabolomics-based study of chemical compositions in cellulase additives derived from a tobacco-origin Bacillus subtilis and their impact on tobacco sensory attributes - Xiaofeng Chen; Teng Long; Shixin Huang; Yiqiang Chen; Hongliang Lu; Zhenkun Jiang; Cheng Cheng; Jingjing Li; Shanyi Chen; Wei He; Xu Tang; Jianqiang Fan (Archives of Microbiology, 2024)

A complete analysis of the link uncertainty budget for pulsed laser time transfer on China space station - Renfang Geng; Zhibo Wu; Yong Huang; Zhien Cheng; Rongzong Yu; Kai Tang; Haifeng Zhang; Wendong Meng; Huarong Deng; Mingliang Long; Si Qin; Zhongping Zhang (Advances in Space Research, 2024)

Sustainable, efficient, and synergistic photocatalytic degradation toward organic dyes and formaldehyde gas via Cu2O NPs@wood - Lingling Wang; Maojie Tang; Haiqiu Jiang; Jiahui Dai; Ruifeng Cheng; Bei Luo; Long Yang; Guanben Du; Wei Gao (Journal of Environmental Management, 2024)

Field and numerical investigation of soil hydro-thermal response to the climatic conditions in southern China considering soil heterogeneity - Zhao-Jun Zeng; Chao-Sheng Tang; Qing Cheng; Ni An; Zhan-Ming Yang; Xu-Long Gong; Xiao-Ying Chen (Engineering Geology, 2024)

Establishment and characterization of DPC-X4: a novel mixed-type ampullary cancer cell line - Changpeng Chai; Huan Tang; Jianfeng Yi; Lu Li; Cheng Yu; Yuanhui Su; Long Miao; Zhenzhen Ye; Zhengfeng Wang; Wei Luo; Jinjing Hu; Hui Zhang; et al. (Human Cell, 2024)

Thermoelectrics and thermocells for fire warning applications - Zhaofu Ding; Chunyu Du; Wujian Long; Cheng-Fei Cao; Lirong Liang; Long-Cheng Tang; Guangming Chen (Science Bulletin, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Effects of spray drying and freeze drying on the structure and emulsifying properties of yam soluble protein: A study by experiment and molecular dynamics simulation - Hao-nan Nie; Hui Dong; Yun-long Chen; Miao-miao Hao; Jia-nan Chen; Zi-cheng Tang; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Chemistry, 2023)

The Effect of Food Deprivation on Foraging Behavior and Digestive and Metabolic Capacities of the Chinese Mitten Crab, Eriocheir sinensis - Qiaolin Long; Jian Liu; Yunfei Sun; Zhigang Yang; Boping Tang; Yongxu Cheng (Fishes, 2023)
Food deprivation is a common stress in crustaceans that can affect their behavior and physiology. In this study, a video recording analysis system was used to compare the predation rate and behavior of the Chinese mitten crab, Eriocheir sinensis, foraging on the freshwater snail, Bellamya quadrata, under different degrees of food deprivation. The activities of lactate dehydrogenase, α-amylase, pepsin, and lipase in the hepatopancreas of crabs were determined after food deprivation for 0, 3, 9, and 15 days. The results showed that the predation and encounter rates of E. sinensis increased and then decreased with an increase in food deprivation time. The proportion of stationary time of E. sinensis initially decreased and then increased, whereas the proportion of searching and handling time increased initially and then decreased. There was a significant difference in the probability of capture upon encountering; however, food deprivation did not significantly affect the probability of consumption upon capture. Under food deprivation, the proportion of E. sinensis crushing tactics after nine-day food deprivation was significantly lower than that in the first nine days. Lactate dehydrogenase activity in the E. sinensis hepatopancreas after food deprivation was significantly higher than that in those not subjected to food deprivation, and the activities of α-amylase and pepsin in the hepatopancreas were consistent with the predation rate trend, showing an initial increase followed by a decrease. In conclusion, different degrees of food deprivation significantly affected the predation cycle of E. sinensis on B. quadrata. These results lay a solid foundation for further studies on the foraging behavioral ecology of E. sinensis and provide important information for improving E. sinensis production.

Gender-specific effects of prenatal mixed exposure to serum phthalates on neurodevelopment of children aged 2–3 years:the Guangxi Birth Cohort Study - Yuan Zheng; Longman Li; Hong Cheng; Shengzhu Huang; Xiuming Feng; Lulu Huang; Luyun Wei; Dehao Cao; Sida Wang; Long Tian; Weijun Tang; Caitong He; et al. (Environmental Science and Pollution Research, 2022)

Development and use of a reverse transcription insulated isothermal PCR assay for detection and characterization of bovine torovirus in yaks - Long Zhao; Guoqing Shao; Cheng Tang; Hua Yue (Archives of Virology, 2021)

2,3,5,6-Tetramethylpyrazine protects retinal photoreceptors against endoplasmic reticulum stress by modulating ATF4-mediated inhibition of PRP aggregation - Hao Huang; Xiaobo Zhu; Hao Cheng; Xielan Kuang; Chongde Long; Xizhi Deng; Yuxiu Zou; Han Zhang; Yue Xing; Xiangtian Ling; Renchun Wang; Han Tang; et al. (Journal of Molecular Medicine, 2021)

An emerging novel bovine coronavirus with a 4-amino-acid insertion in the receptor-binding domain of the hemagglutinin-esterase gene - Keha-mo Abi; Qi Zhang; Bin Zhang; Long Zhou; Hua Yue; Cheng Tang (Archives of Virology, 2020)

Retraction Note to: An assessment of transgenomics as a tool for gene discovery in Populus euphratica Oliv. - Jing Zhou; Xin Liu; Shu-Tang Zhao; Jian-Jun Hu; Jie-Wei Zhang; Jie-Hua Wang; Xiao-Peng Peng; Xiao-Li Qi; Tie-Long Cheng; Meng-Zhu Lu (Plant Molecular Biology, 2018)

RETRACTED ARTICLE: An assessment of transgenomics as a tool for gene discovery in Populus euphratica Oliv. - Jing Zhou; Xin Liu; Shu-Tang Zhao; Jian-Jun Hu; Jie-Wei Zhang; Jie-Hua Wang; Xiao-Peng Peng; Xiao-Li Qi; Tie-Long Cheng; Meng-Zhu Lu (Plant Molecular Biology, 2018)

The regulation of skeletal muscle fiber-type composition by betaine is associated with NFATc1/MyoD - Jingjing Du; Linyuan Shen; Peiwen Zhang; Zhendong Tan; Xiao Cheng; Jia Luo; Xue Zhao; Qiong Yang; Hao Gu; An’an Jiang; Jideng Ma; Qianzi Tang; et al. (Journal of Molecular Medicine, 2018)

Photosynthetic tolerance to non‐resource stress influences competition importance and intensity in an invaded estuary - Long Tang; Amelia A. Wolf; Yang Gao; Cheng Huan Wang (Ecology, 2018)
In an attempt to clarify the role of environmental and biotic interactions on plant growth, there has been a long‐running ecological debate over whether the intensity and importance of competition stabilizes, increases or decreases across environmental gradients. We conducted an experiment in a Chinese estuary to investigate the effects of a non‐resource stress gradient, soil salinity (from 1.4‰ to 19.0‰ salinity), on the competitive interactions between native Phragmites australis and invasive Spartina alterniflora . We linked these effects to measurements of photosynthetic activities to further elucidate the underlying physiological mechanism behind the competitive interactions and the driver of invasion. The experiments revealed that while biomass of both species decreased in the presence of the other, competition did not alter photosynthetic activity of either species over time. P. australis exhibited high photosynthetic activity, including low chlorophyllase activity, high chlorophyll content, high stomatal conductance and high net photosynthetic rate, at low salinity. Under these conditions, P. australis experienced low competitive intensity, leading to high biomass production and competitive exclusion of S. alterniflora . The opposite was observed for S. alterniflora : while competitive intensity experienced by P. australis increased with increasing salinity, and photosynthetic activity, biomass, competitive dominance and the importance of competition for P. australis growth decreased, those of S. alterniflora were stable. These findings demonstrate that S. alterniflora invasion driven by competitive exclusion are likely to occur and expand in high salinity zones. The change in the nature of competition along a non‐resource stress gradient differs between competitors likely due to differences in photosynthetic tolerance to salinity. The driver of growth of the less‐tolerant species changes from competition to non‐resource stress factors with increasing stress levels, whereas competition is constantly important for growth of the more‐tolerant species. Incorporating metrics of both competition intensity and importance, as well as linking these competitive outcomes with physiological mechanisms, is crucial to understanding, predicting, and mediating the effects of invasive species in the future.

The effect of electron competition on chromate reduction using methane as electron donor - Pan-Long Lv; Liang Zhong; Qiu-Yi Dong; Shi-Lei Yang; Wei-Wei Shen; Quan-Song Zhu; Chun-Yu Lai; An-Cheng Luo; Youneng Tang; He-Ping Zhao (Environmental Science and Pollution Research, 2018)

Controlling mechanism of absence seizures by deep brain stimulus applied on subthalamic nucleus - Bing Hu; Yu Guo; Xiaoqiang Zou; Jing Dong; Long Pan; Min Yu; Zhejia Yang; Chaowei Zhou; Zhang Cheng; Wanyue Tang; Haochen Sun (Cognitive Neurodynamics, 2018)

Comprehensive Analysis of R2R3-MYB Genes During Adventitious Root Formation in Cuttings of Morus alba - Xiao Long Du; Xu Cao; Chao Rui Yin; Zhuang Tang; Wei Du; Yue Yuan Ban; Jia Ling Cheng (Journal of Plant Growth Regulation, 2017)

Mechanical Model for Predicting Closure Behavior of Rock Joints Under Normal Stress - Zhi-Cheng Tang; Quan-Sheng Liu; Cai-Chu Xia; Ying-Long Song; Ji-Hui Huang; Chun-Bo Wang (Rock Mechanics and Rock Engineering, 2014)

New Peak Shear Strength Criterion of Rock Joints Based on Quantified Surface Description - Cai-Chu Xia; Zhi-Cheng Tang; Wei-Min Xiao; Ying-Long Song (Rock Mechanics and Rock Engineering, 2014)

Combined effect of five single nucleotide polymorphisms related to IL23/Th17 pathway in the risk of psoriasis - Xianyong Yin; Hui Cheng; Ran Zhang; Xing Fan; Fusheng Zhou; Long Jiang; Xianfa Tang; Gang Chen; Xianbo Zuo; Xiaodong Zheng; Sen Yang; Xuejun Zhang (Immunogenetics, 2014)

Short hairpin RNA targeting NP mRNA inhibiting Newcastle disease virus production and other viral structural mRNA transcription - Hua Yue; Shu Deng; Fa-long Yang; Ding-fei Li; An-jing Fu; Fan Yang; Cheng Tang (Virus Genes, 2009)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Effect of the neuroprotective agent riluzole on intracellular Ca 2+ levels in IMR32 neuroblastoma cells - Jue-Long Wang; Kam-Chung Lee; Kwong-Yui Tang; Ti Lu; Cheng-Ho Chang; Chik-Keung Chow; Wei-Chuan Chen; Warren Su; Yee-Ping Law; Chung-Ren Jan (Archives of Toxicology, 2001)

Tamoxifen-induced Ca 2+ mobilization in bladder female transitional carcinoma cells - Hong-Tai Chang; Jong-Khing Huang; Jue-Long Wang; Jin-Shiung Cheng; Kam-Chung Lee; Yuk-Keung Lo; Muh-Chiou Lin; Kwong-Yui Tang; Chung-Ren Jan (Archives of Toxicology, 2001)